The modern teens’ socio-cultural development diagnostics and interaction between family and school - Tanaeva, Zamfira R.; Smagliy, Tatyana I.; Anatoly A. Pavlicenco, Tatyana V. Zueva,; Elizarova, Elena I.; Natalia Y. Kyfik, Saule G. Kanapina, Maira S. Sapieva, (Opción, 2019)
The purpose of the study is to investigate the modern teens’ socio-cultural development diagnostics and interaction between family and school via survey methods. As a result, the dynamics of a teen’s socio-cultural development in the interaction between the family and the school is considered, the main determinants that prevent this process are defined, and the mechanisms of the teens’ socio-cultural development organization within the cultural-leisure activity are identified. In conclusion, the teens’ personal socio-cultural development is realized by stimulating them to internalize the national cultural code, universal human values, etc.